Ascites in a Labrador retriever puppy with Babesiosis – A case report - P.Udhayabanu; Mayur M. Jadav; K. Mahendran (Indian Journal of Veterinary Medicine, 2024)
A 2-month-old male Labrador puppy was presented to Referral Veterinary Polyclinic-Teaching Veterinary Clinical Complex, ICAR- Indian Veterinary Research Institute with a history of inappetence and bilaterally distended abdomen for a period of 15 days. On physical examination, generalized weakness, pale mucous membrane, pyrexia, tachycardia, tachypnea and fluid thrill on the abdomen were noticed. Severe anemia, reduced hematocrit, neutrophilic leukocytosis, hypoproteinemia, hypoalbuminemia and elevated liver enzymes were noticed in haemato-biochemical examination. Babesia sp.was detected in blood smear examination. Ultrasound examination revealed hepatomegaly and ascites. Based on these findings, the case was diagnosed as ascites due to Babesiosis. Forty ml of whole blood was transfused and the animal was treated with Inj. Dextrose, Inj. Imidocarb, Inj. Furosemide for 2 days. Case was discharged with the advice of continuing the treatment with triple drug therapy (doxycycline, clindamycin and metronidazole) for 10 days, hepato-protectant (Susp. Silybon®), haematinic (Syp. Hemobest®) and diuretics (Spironolactone and furosemide combination) orally for 30 days at home and regular follow up. The animal showed uneventful recovery following treatment.